Frugal forensics: addressing the challenges of sustainable forensic science service provision - Lewis, Simon W.; Heavey, Anna L.; Bouzin, Jemmy T.; Lopes, Thais; Sauzier, Georgina; Parrish, Jessie (Taylor & Francis, 2024)
Forensic science is an essential service in supporting criminal investigations and the justice system. It also has global humanitarian, peace and security dimensions making it a key factor in achieving several United Nations Sustainable Development Goals. Despite forensic science’s universal value, many jurisdictions are at a stark disadvantage in the continued development of forensic science with limitations in resourcing and technological capabilities. To address this challenge, we have proposed the concept of frugal forensics, which we have applied to latent fingermark detection. We argue that the sustainable provision of forensic science must become a critical element of future international discourse.